PENGARUH PENAMBAHAN JENIS PAKAN SUMBER PROTEIN PADA RANSUM BERBASIS LIMBAH DAN HIJAUAN KELAPA SAWIT TERHADAP KONSUMSI, PERTAMBAHAN BOBOT, DAN EFISIENSI KELINCI LOKAL JANTAN - Darwin Indra Saputra; Liman ,; Muhtarudin . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of this study was to determine the effect ofthe type of protein source feed material in the ration, based on palm oil waste and forage against male local rabbits weight increase. This study use completely randomized design with three treatment and four group. The rabbits that used was male local rabbits with body weight average on group 1) 210-250g, group 2) 260-300g, group 3) 310-350, group 4)360-400g. The treatment that given in this study was R0= basalt ration ( palm oil fiber 0,3%, palm oil leaf forage 0,7 % and palm oil oilcake 27 %, bran 32%, corn 40%), R1 = R0 + 15% cassava leaf, R2 = R1 + 3% chicken feather flour. This study data be examined with analysis of variance and followed with least significant difference test. The result of this study showed that type adding feed protein based on palm oil waste and forage does not significantly (effect) with male local rabbits weight increase. Based on palm waste and forage that added with chicken feather flour hydrolized protein source materials (R2) was the best treatment to increase male local rabbits weight. Keywords : Cassava Leave, Chicken Feather Flour Hydrolized, Male Local Rabbits, Palm Oil Waste and Forage, Rabbits Weight Increase.